Improving the Anaerobic Digestion of Swine Manure through an Optimized Ammonia Treatment: Process Performance, Digestate and Techno-Economic Aspects - Anna Lymperatou; Niels B. Rasmussen; Hariklia N. Gavala; Ioannis V. Skiadas (Energies, 2021)
Swine manure mono-digestion results in relatively low methane productivity due to the low degradation rate of its solid fraction (manure fibers), and due to the high ammonia and water content. The aqueous ammonia soaking (AAS) pretreatment of manure fibers has been proposed for overcoming these limitations. In this study, continuous anaerobic digestion (AD) of manure mixed with optimally AAS-treated manure fibers was compared to the AD of manure mixed with untreated manure fibers. Due to lab-scale pumping restrictions, the ratio of AAS-optimally treated manure fibers to manure was only 1/3 on a total solids (TS) basis. However, the biogas productivity and methane yield were improved by 17% and 38%, respectively, also confirming the predictions from a simplified 1st order hydrolysis model based on batch experiments. Furthermore, an improved reduction efficiency of major organic components was observed for the digester processing AAS-treated manure fibers compared to the non-treated one (e.g., 42% increased reduction for cellulose fraction). A preliminary techno-economic analysis of the proposed process showed that mixing raw manure with AAS manure fibers in large-scale digesters could result in a 72% increase of revenue compared to the AD of manure mixed with untreated fibers and 135% increase compared to that of solely manure.